Morphology systems for databases on buildings with curved façades - K. Vollers (Challenging Glass Conference, 2010)
Buildings are emerging with an increasing degree of geometrical variation. As yet no scheme categorises data on the basis of non-orthogonal geometries applied. The author proposes an easily accessible morphological scheme which for example, enables data to be retrieved on sustainable performance of glass types as related to the distinctive building shapes. The scheme focuses on high-rises; in a later version buildings with less prominent vertical character will be included. The shaping of most non-orthogonal buildings is related to developments in modeling software. The morphological scheme is based on software manipulations to describe shaping, not on mathematical formulae. As software develops, new ways of form generating and new shapes emerge. In consequence the shaping scheme gradually will be updated. The scheme can be made accessible both in printed version by illustrations, as in digitised form, for example by keywords. The scheme is illustrated by examples of overall shaping. Trends in the applications of types of curved glass are briefly discussed.